Ammonium catalyzed cyclitive additions: evidence for a cation-pi interaction with alkynes - Nagy, Edith; St Germain, Elijah; Cosme, Patrick; Maity, Pradip K.; Terentis, Andrew C.; Lepore, Salvatore D. (Chemical Communications, 2016)
The addition of carbamate nitrogen to a non-conjugated carbon-carbon triple bond is catalyzed by an ammonium salt leading to a cyclic product. Studies in homogeneous systems suggest that the ammonium agent facilitates nitrogen-carbon bond formation through a cation-p interaction with the alkyne unit that, for the first time, is directly observed by Raman spectroscopy.